The Practical Understanding of Contextual Islamic Religious Education Based on Local Marine Wisdom - Siti Nurjanah; Raharjo; Irfa'i Alfian Mubadilla; Titah Maulida Wanodyo (Universitas Nahdatul Ulama Surabaya, 2026)
This research aims to examine the implementation of Islamic Religious Education (PAI) learning integrated with coastal local wisdom, to assess students’ levels of practical understanding following the learning process, and to identify the dominant and non-dominant dimensions of that understanding. The study was conducted at a Nahdlatul Ulama–affiliated vocational secondary school located in Palang, Tuban, East Java, Indonesia, employing a sequential explanatory mixed-methods design. Data collection involved the administration of a conceptual test for quantitative analysis, which was analysed using descriptive statistics, as well as classroom observations, interviews, and document analysis for qualitative inquiry. The quantitative findings indicate that students achieved a high level of mastery in the cognitive dimension (Mean = 7.73; 77.3%), followed by the applicative dimension (Mean = 5.60; 56%). The reflective–affective dimension demonstrated the lowest level of mastery (Mean = 4.80; 48%). Qualitative findings reveal that the integration of coastal local wisdom into PAI learning has been implemented primarily at the conceptual and contextual levels, through the use of illustrations and narratives related to coastal life. However, this integration has not yet extended to the experiential and reflective levels. The composite analysis suggests that while students’ cognitive understanding is relatively strong, their reflective–affective understanding remains limited due to insufficient application of experiential learning approaches, reflectively oriented pedagogy, and authentic assessment practices. This study is limited by its focus on a single vocational secondary school and a relatively small sample size. Therefore, future research is recommended to involve broader educational contexts and to employ experimental or design-based research approaches in order to develop and test pedagogical models that emphasize experiential and reflective dimensions of PAI learning within coastal cultural settings.